The Importance Of Financial Inclusion For Women’s Empowerment In Seaweed Industry As A Potential Resource For Blue Economy Development - Lerissa Daniela; Tasya Zahwa Prayoga; R. S. Bayu Mangkurat; Jonathan Lampatar Siregar; Filda Rahmiati (UNIVERSITAS PAKUAN, 2024)
This study focuses on the seaweed sector and women's economic empowerment while providing an outline of the Blue Economy idea and its current situation in Lancang island, Kepulauan Seribu, Indonesia. The Blue Economy is gaining popularity as a way to protect marine ecosystems while assuring nation’s economic success and encourages the sustainable use of ocean resources. Indonesia, the biggest archipelago in the world, has a considerable blue economy potential. This research underlines the significance of striking a balance between economic expansion, the preservation of marine biodiversity, and the welfare of coastal communities. It emphasizes the responsibilities played by women in the seaweed sector and their restricted access to financial institutions. Furthermore, the study underlines the importance of additional research to improve long-term economic resilience by empowering women in the seaweed sector, contribute to long-term community development, and promoting financial inclusion. Though vital, seaweed women face several obstacles, including inadequate financial services and decision-making power. These constraints must be overcome to maximize the blue economy development. To conclude, financial inclusion, especially through cooperatives and digital financial services, is key to closing this gap. Indonesia and other nations can maximize the blue economy's potential while promoting sustainable development and empowerment by prioritizing financial inclusion